Towards Unified Design Guidelines for New Interfaces for Musical Expression. - Paine, Garth (Organised Sound, 2009)
The use of a laptop computer for musical performance has become widespread in the electronic music community. It brings with it many issues pertaining to the communication of musical intent. Critics argue that performances of this nature fail to engage audiences because many performers use the mouse and/or computer keyboard to control their musical works, leaving no visual cues to guide the audience as tother correlation between performance gestures and musical outcomes. The author will argue that interfaces need to communicate something of their task and that cognitive affordances (Gibson 1979) associated with the performance interface become paramount if the musical outcomes are to be perceived as clearly tied to real-time performance gestures -in other words, that the audience are witnessing the creation of the music in that moment as distinct to the manipulation of pre-recorded or pre-sequenced events. Interfaces of his kindled themselves particularly to electro acoustic and computer music performance where timbre, texture and morphology may be paramount.